ANALISIS PENGARUH KUALIFIKASI KONTRAKTOR TERHADAP KUALITAS PEKERJAAN PROYEK KONSTRUKSI DI KOTA SEMARANG - Anggraini, Lila; Rahmawati, Diah; Widorini, Trias (Jurnal Pengembangan Rekayasa dan Teknologi, 2017)
The law on construction services has been in effect for seventeen years, but the world of construction services in Indonesia has not been very exciting, especially for construction workers for large-scale and high-tech projects. Indonesia's workforce is still considered not to have capability comparable with foreign construction workforce.To realize the success of quality buildings and able to function as planned, needed human resources of good quality as well.And the professional ability of the construction workforce is evidenced by the possession of a skill or skill certificate. As mandated by the Construction Services Act No. 18 of 1999 article 9. that any individual employed by a business entity as a construction planner or supervisor of a particular construction or energy in a construction business enterprise shall have a certificate of expertise.Based on the research factors that most affect the application of Construction Services Act of 1999 memnai certificate of competence of experts on the implementation of construction work.is a factor of human resources such as education experts, experience, training, age and ownership of certificates. Another factor is the method of implementation of work such as coordination and decision making, while the political factor is the regulation of rules and leadership factors, such as motivation and awards To know how far and how big the role of these construction service experts in achieving the success of construction work, so much in demand by both local and foreign workers, it is deemed necessary to research the role of experts in contributing to the success of a construction work.Therefore it is necessary to develop further research on the readiness of experts in terms of the fulfillment of the requirements and expertise, in order to obtain the predicate of professional engineers or professional engineers through certification of expertise held by professional associations that followed.